2013
DOI: 10.1002/ange.201308377
|View full text |Cite
|
Sign up to set email alerts
|

Helicenes with Embedded Phosphole Units in Enantioselective Gold Catalysis

Abstract: This paper discloses the first uses of phosphahelicenes as chiral ligands in transition-metal catalysis. Unlike all known helical phosphines used so far in catalysis, the phosphorus function of phosphahelicenes is embedded in the helical structure itself. This crucial structural feature originates unprecedented catalytic behaviors and efficiency. An appropriate design and fine tuning allowed both high catalytic activity and good enantiomeric excesses to be attained in the gold promoted cycloisomerizations of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 75 publications
0
42
0
Order By: Relevance
“…Thus, helicenes can be utilized them a broad range of applications in chiral materials, in the chiral recognition of biomolecules, and in asymmetric synthesis161718192021222324. More specifically, chiral helicene-based trivalent phosphorus ligands are efficient asymmetric inductors in metal-catalyzed asymmetric reactions and show good to excellent enantioselectivities252627282930313233. We hypothesized that novel helicenylphosphine ligands, which induce intramolecular metal-arene interactions, could be used to construct an efficient chiral catalytic system.…”
mentioning
confidence: 99%
“…Thus, helicenes can be utilized them a broad range of applications in chiral materials, in the chiral recognition of biomolecules, and in asymmetric synthesis161718192021222324. More specifically, chiral helicene-based trivalent phosphorus ligands are efficient asymmetric inductors in metal-catalyzed asymmetric reactions and show good to excellent enantioselectivities252627282930313233. We hypothesized that novel helicenylphosphine ligands, which induce intramolecular metal-arene interactions, could be used to construct an efficient chiral catalytic system.…”
mentioning
confidence: 99%
“…Surprisingly, helicenes with appended phosphorus functions have been rarely used in asymmetric organo‐ and organometallic catalysis, giving overall rather disappointing results 2. On the other hand, we have demonstrated that helicenes in which a phosphorus function is embedded into the helical scaffold itself (phosphahelicenes)3, 4 offer new perspectives in these fields 57. Indeed, especially designed phospha[6]helicenes, typified by IV in Figure 1, have been established as promising ligands in the challenging field of enantioselective gold catalysis, through studies on the cycloisomerization of 1,6‐enynes 5.…”
Section: Methodsmentioning
confidence: 99%
“…The enantioselective version was accomplished by the use of traditional biaryl diphosphine ligands. This procedure provided a complementary method for preparing chiral fused cyclopropane rings, in contrast to other enantioselective cyclopropanations, which were usually limited to construction of bicyclo[3.1.0]hexane or bicyclo[4.1.0]heptene scaffolds.…”
Section: Cycloaddition Reactionsmentioning
confidence: 99%
“…The HelPHOS–gold complexes, such as Au19 , Au20 , Au21 ,and Au22 , developed by Marinetti, Voituriez, Licandro, and co‐workers showed good performances in the enantioselective cycloisomerizations of a variety of nitrogen‐tethered 1,6‐enynes (Scheme ). They initially found that the chiral gold complexes Au19 – 21 , which incorporate meta ‐fused phosphole units and an α‐aryl substituent relative to the phosphorus atom, effected the cycloisomerization of 1,6‐enyene 314 a with good enantioselectivity . Later, another similar phosphathiahelicene ligand‐coordinated chiral gold complex Au22 was synthesized .…”
Section: Cycloisomerization or Cyclization Of Enynesmentioning
confidence: 99%